Napoleon Quince at ang malisya sa pagtikim ng kinse años - Arao, Danilo A. (2004)
"Nakatikim ka na ba ng kinse años?" (Have you ever tasted a 15-year old?) is a question from a billboard advertisement of Napoleon Quince that triggered numerous protests from women's and children's groups from February to April 2004. This investigative report analyzes the arguments for and against the billboard advertisement and contextualizes the issues raised vis-a-vis the status of women and children in society. The report observes that the advertisement's double meaning is quite apparent despite Destileria Limtuaco's claims to the contrary. It is exploitative not just of women but also of children, particularly 15-year old girls. The advertisement reflects patriarchy in society and sexism in liquor advertisements. It is proof of how businesses are wont to exploit women and children just to sell their products.